1995
DOI: 10.1103/physrevlett.75.1872
|View full text |Cite
|
Sign up to set email alerts
|

Topological Censorship[Phys. Rev. Lett. 71, 1486 (1993)]

Abstract: All three-manifolds are known to occur as Cauchy surfaces of asymptotically flat vacuum spacetimes and of spacetimes with positive-energy sources. We prove here the conjecture that general relativity does not allow an observer to probe the topology of spacetime: any topological structure collapses too quickly to allow light to traverse it. More precisely, in a globally hyperbolic, asymptotically flat spacetime satisfying the null energy condition, every causal curve from J ( − to J ( + is homotopic to a topolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
156
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(164 citation statements)
references
References 8 publications
7
156
0
1
Order By: Relevance
“…This relies on the Gauss-Bonnet theorem applied to the (two dimensional) horizon and therefore does not generalize to higher dimensions. An alternative proof in four dimensions is based on the notion of "topological censorship" [30]. Consider a spacelike slice Σ that intersects the future event horizon and let H denote the intersection.…”
Section: Black Holes With Fewer Symmetriesmentioning
confidence: 99%
“…This relies on the Gauss-Bonnet theorem applied to the (two dimensional) horizon and therefore does not generalize to higher dimensions. An alternative proof in four dimensions is based on the notion of "topological censorship" [30]. Consider a spacelike slice Σ that intersects the future event horizon and let H denote the intersection.…”
Section: Black Holes With Fewer Symmetriesmentioning
confidence: 99%
“…This condition applied to twodimensional manifolds determines uniquely the topology. The "topological censorship theorem" of Friedmann, Schleich and Witt is another indication of the impossibility of non spherical horizons [37,38]. However, when the asymptotic flatness of spacetime is violated, there is no fundamental reason to forbid the existence of static or stationary black holes with nontrivial topologies.…”
Section: Introductionmentioning
confidence: 99%
“…That is, general relativity does not allow an observer to probe the topology of spacetime: Any topological structure collapses too quickly to allow light to traverse it. Later on, however, they found that nontrivial topologies can be observed passively [2]. The black holes with toroidal topology have indeed been found numerically in the gravitational collapse [3], although such a topological structure is temporal.…”
mentioning
confidence: 99%